2020
DOI: 10.1136/bmjdrc-2019-000763
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients with end-stage renal disease hospitalized with diabetes ketoacidosis

Abstract: IntroductionThere is limited evidence to guide management in patients with end-stage renal disease (ESRD) on chronic hemodialysis admitted with diabetes ketoacidosis. Thus, we investigated the clinical characteristics and outcomes of patients with ESRD admitted with diabetic ketoacidosis (DKA).MethodsIn this observational study, we used International Classification of Diseases Ninth/Tenth Revision codes to identify adult (aged 18–80 years) patients admitted to Emory University Hospitals between 1 January 2006 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…We found a higher incidence of DKA in females in the ESKD group (52.4% vs. 48.97%) than in the patients with no CKD/ ESKD. Other studies supported this finding where DKA with ESKD was more prevalent in females [ 6 ]. Several international studies have shown that the female sex is an independent risk factor for developing DKA regardless of ESKD [ 11 - 14 ].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…We found a higher incidence of DKA in females in the ESKD group (52.4% vs. 48.97%) than in the patients with no CKD/ ESKD. Other studies supported this finding where DKA with ESKD was more prevalent in females [ 6 ]. Several international studies have shown that the female sex is an independent risk factor for developing DKA regardless of ESKD [ 11 - 14 ].…”
Section: Discussionsupporting
confidence: 69%
“…Diabetic ketoacidosis (DKA) is one of the most acute complications related to diabetes [ 4 ]. Treatment of DKA with ESKD or CKD has been associated with an increased risk of hypoglycemia and volume overload [ 6 , 7 ]. If not treated promptly, patients can develop severe metabolic acidosis and other complications [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows presenting values for [Glu], [Na], tonicity, and corrected [Na] in reports of DKA ( 66 171 ), HHS ( 3 , 9 , 13 , 75 78 , 110 , 129 , 169 , 172 251 ), and hyperglycemia in chronic kidney disease (CKD) stage V ( 12 , 16 , 47 49 , 156 , 171 , 252 277 ), which was included in Table 2 as the control group because it causes limited or no water and electrolyte losses through osmotic diuresis. All but three of the cases in this last group were on maintenance dialysis.…”
Section: Derivations Of the Corrected [Na] In Hyperglycemiamentioning
confidence: 99%
“…In DKA the overall mean corrected [Na] was within the normal range of [Na] (137–143 mmol/L). Among DKA series with ≥10 cases, mean corrected [Na] was in the eunatremic range in 45 series ( 66 – 69 , 71 , 74 , 75 , 80 , 83 , 84 , 90 , 91 , 93 , 104 106 , 108 , 109 , 112 , 113 , 118 , 120 , 122 , 125 127 , 129 , 135 , 137 , 138 , 140 , 143 146 , 151 , 155 , 156 , 158 , 160 , 163 165 , 168 171 ) reporting 6,355 episodes, including the pivotal PECARN study in which mean corrected [Na] was 140.8 mmol/L in one study group and 140.7 mmol/L in each of the other three study groups ( 163 ); and in the hypernatremic range in the remaining 18 series ( 74 , 76 , 78 , 80 , 85 , 91 , 93 , 98 , 100 102 , 104 , 116 , 120 , 129 , 133 , 139 , 169 ) reporting 1,301 episodes. Thus, although many patients have water deficits in excess of sodium and potassium deficits, an equal or even larger number of patients do not have excessive water deficits at presentation with DKA.…”
Section: Derivations Of the Corrected [Na] In Hyperglycemiamentioning
confidence: 99%